Cellulose nanocrystals coated with a tannic acid-Fe3+ complex as a significant medium for efficient CH4 microbial biotransformation. (15th April 2021) - Kang, Eungsu; Je, Hwa Heon; Moon, Eunjoo; Na, Jeong-Geol; Kim, Min Sik; Hwang, Dong Soo; Choi, Yoo Seong
Graphical abstract: Highlights: A cellulose nanocrystals-based nanofluid was prepared for microbial CH4 utilization. CH4 gas bubbles were stabilized in the nanofluid without any agglomeration. The CH4 solubility and the kL a were enhanced in the nanofluid. The cellulose nanocrystals improved the cell growth rate and metabolite production. The nanofluid was not cytotoxic and did not influence cell morphology. Abstract: Microbial biotransformation of CH4 gas has been attractive for the production of energy and high-value chemicals. However, insufficient supply of CH4 in a culture medium needs to be overcome for the efficient utilization of CH4 . Here, we utilized cellulose nanocrystals coated with a tannic acid-Fe 3+ complex (TA-Fe 3+ CNCs) as a medium component to enhance the gas-liquid mass-transfer performance. TA-Fe 3+ CNCs were well suspended in water without agglomeration, stabilized gas bubbles without coalescence, and increased the gas solubility by 20 % and the kL a value at a rapid inlet gas flow rate. Remarkably, the cell growth rate of Methylomonas sp. DH-1 as model CH4 -utilizing bacteria improved with TA-Fe 3+ CNC concentration without any cytotoxic or antibacterial properties, resulting in higher metabolite production ability such as methanol, pyruvate, formate, and succinate. These results showed that TA-Fe 3+ CNCs could be utilized as a significant component in the culture medium applicable as a promising nanofluid for efficient CH4 microbial biotransformation.